Effects of temperature on flowering overlaps between an alpine plant (Plantago hakusanensis Koids.) and a domestic alien plant (P. asiatica L.) - Sano, Saki; Nakayama, Yuichiro; Nogami, Tatsuya; Yagyu, Atsushi (Journal of Weed Science and Technology, 2023)
In the subalpine zone of Mt. Hakusan in Japan, an endemic alpine plant Plantago hakusanensis Koidz. flowers twice a year, and the second flowering event overlaps with P. asiatica L., a domestic alien plant flowering. As a result, interspecific pollination between P. hakusanensis and P. asiatica may occur. In this chapter, the effects of temperature on flowering in both species are examined through experiments.In P. hakusanensis, a second flowering event occurred in both low- and high-temperature treatments. Based on the relationship between the position of the inflorescence and the timing of flowering, P. hakusanensis forms flower buds during the growing season (preformation), overwinters with dormant flower buds, and blooms immediately after snow melts the following year. However, some flower buds reached flowering during the growing season; therefore, P. hakusanensis had a second flowering event. In contrast, P. asiatica forms inflorescences during the growing season and blooms throughout the year. Both species initiated flowering earlier, and more inflorescences were formed in the high-temperature treatment than in the low-temperature treatment. The distribution of flowering based on the effective total temperature greatly overlapped between the two species. These results suggest that flowering is temperature-dependent. It is thought that as temperature increases, the opportunity for interspecific pollination increases owing to the prolonged flowering period and increased overlap in the amount of flowering of both species, thus facilitating the occurrence of interspecific hybridization.